Impact of inhalation therapy on the incidence of carious lesions in patients with asthma and COPD (Journal of Applied Oral Science, 2017)
Objective: The aim of this study was to investigate the incidence of carious lesions, the amount of salivary flow rate and pH value in patients with asthma and chronic obstructive pulmonary diseases (COPD), using inhalation therapy. The obtained results were compared with the results of adult healthy subjects, forming a control group. Material and Methods: The study included 80 participants aging between 18 and 65 years. The experimental group (EG) was comprised of 40 participants, previously diagnosed with asthma or COPD undergoing inhalation therapy for more than five years. The control group (CG), comprised of 40 participants, mirrored the same age and gender status of the EG. Dental status was determined by decayed, missing, and filled teeth (DMFT index). Quantity and pH value of saliva were determined in the laboratory. Results: In the EG, the mean value of the salivary flow rate and pH value were statistically significantly lower than in the CG (p<0.001). Patients in the EG had a higher value of DMFT index when compared with the CG, although the difference was not statistically significant (p=0.199). Mean number of decayed teeth, as well as missing teeth, in the EG was statistically significantly higher than in the CG (p<0.001). Mean number of filled teeth in the EG was statistically significantly lower than in the CG (p<0.001). Conclusion: It was found that patients undergoing inhalation therapy face increasing risk of dental caries due to the lower salivary flow rate and pH value along with the inhalation therapy. They should receive intensive preventive care, including oral hygiene instruction and dietary advice.